Optimization of Conditions for the Preparation of Activated Carbon from Lapsi (Choerospondias axillaris) Seed Stone Using ZnCl2 - Joshi, Rinita Rajbhandari (Journal of the Institute of Engineering, 2016)
Activated carbon was prepared from Lapsi (Choerospondias axillaries ) seed stone by chemical activation method using ZnCl2. The effect of experimental variables; ZnCl2 ratio, temperature and carbonization time on the quality of the activated carbon were systematically invested by determining the carbon yield, iodine number, methylene blue number, surface area and pore volume. Lapsi seed stone powder (LSP) of particle size < 300 μm was used to prepare activated carbon under N2 atmosphere. An increase in ZnCl2 ratio in general increased the iodine number and methylene blue number, but on increasing zinc chloride above 50 percentages, iodine and methylene blue number increased only marginally. An increase in carbonization temperature increases the iodine number, methylene blue number, and surface area and pore volume. Increase in carbonization time from 3 hour to 4 hour increases iodine number and methylene blue number and thereafter the increase in iodine number and methylene blue number is gradual. Regarding the carbon yield, it decreases with the ZnCl2 ratio above 50 percent, and the yield also decreases with increase in temperature and carbonization time. Therefore the optimum conditions for the preparation of activated carbon from Lapsi seed stone using ZnCl2 as follows: carbonization temperature of 400°C, zinc chloride ratio as LSP:ZnCl2 equals 1:1, and carbonization time of 4 hour. This resulted an activated carbon with 791 iodine number, 364 methylene blue number, 1167 surface area and 0.65 pore volume. Journal of the Institute of Engineering, 2015, 11(1): 128-139